d‑Band Center Optimization of Ti3C2T x MXene Nanosheets for Ultrahigh NO2 Gas Sensitivity at Room Temperature - Wang, Ying; Fu, Jimin; Hu, Haibo; Ho, Derek (ACS applied materials & interfaces, 2023)
MXene exhibits numerous advantageous properties such as high electronic conductivity, high surface area, and ease of surface modification via tailoring of functional groups. However, the mechanism by which MXene functionalization enhances gas sensing performance has not yet been well understood, let alone the development of a rational sensor design optimization strategy. This work presents a functionalization methodology for MXene based on d-band center modulation, which can be implemented by introducing Fe onto the surface of Ti3C2T x nanosheets, for significantly improved gas sensing response and selectivity. The strategy is demonstrated in the design of gas sensors. The optimized gas sensor shows a response of 50% toward 10 ppm of NO2 at room temperature, which is over 6-fold improvement from its pristine counterpart, an unprecedented performance level among all reported MXene gas sensors. XPS characterizations, valence band analyses, and density functional theory (DFT) calculations all indicate that the underlying enhancement mechanism can be attributed to the tuning of the d-band center energy toward the Fermi level. This work provides a new design strategy based on the optimization of the d-band center energy and adds a much needed systematic and quantitative method to the design of two-dimensional materials based semiconducting gas sensors.